Physical Exercise and Mental Health in Adolescents: Scoping Review - Nathali Carvajal Tello; Alejandro Segura-Ordoñez; Hilary Andrea Banguero Oñate; Juan David Hurtado Mosquera (Revista de Investigación e Innovación en Ciencias de la Salud)
Objective. To identify the most implemented exercises and their prescription, in addition to the effects of exercise on mental health in adolescents.